2004
DOI: 10.1007/s10165-004-0283-8
|View full text |Cite
|
Sign up to set email alerts
|

Discoid lateral menisci in Japanese cadaver knees

Abstract: We undertook a descriptive, observational study to determine the prevalence of the discoid lateral menisci. The relation between the lateral meniscal shapes and the incidence of meniscal tears were studied, and the gender differences in discoid lateral menisci and the similarities of the lateral meniscal shapes in bilateral knees were examined. A total of 602 knees from 306 cadavers were macroscopically analyzed. Altogether, 577 lateral menisci were classified into the following three types: normal type (NM); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…In the study by Ikeuchi2), a discoid lateral meniscus was observed in 16.6% of all knees examined arthroscopically during a 20 year period. In the study by Kato et al3), the prevalence was 33.2% in the 577 lateral menisci obtained from 306 cadavers. Domestically, Seong et al4) found discoid lateral meniscus in 15.3% of patients who underwent arthroscopy and Bin et al5) reported that 15.2% of patients who underwent arthroscopic meniscectomy had this variant, 67% of which were torn.…”
Section: Introductionmentioning
confidence: 91%
“…In the study by Ikeuchi2), a discoid lateral meniscus was observed in 16.6% of all knees examined arthroscopically during a 20 year period. In the study by Kato et al3), the prevalence was 33.2% in the 577 lateral menisci obtained from 306 cadavers. Domestically, Seong et al4) found discoid lateral meniscus in 15.3% of patients who underwent arthroscopy and Bin et al5) reported that 15.2% of patients who underwent arthroscopic meniscectomy had this variant, 67% of which were torn.…”
Section: Introductionmentioning
confidence: 91%
“…Liu et al [ 17 ] reported that 85 % of bilateral DLM manifested homotype. However, bilateral DLM was often observed with only unilateral occurrence of symptoms [ 4 ]. Our results showed that only a small proportion of the patients with unilateral SDLM manifested bilateral symptoms in 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, we occasionally observed asymptomatic DLM in contralateral knees of symptomatic DLM patients, and their bilateral DLM often were of the same type; studies have also supported this finding. Kato et al evaluated 279 Japanese cadavers to study the shape of the menisci, and found that 91 % of DLMs were of the same morphology [ 12 ]. Therefore, when a patient presents with DLM in one knee, it is important to carefully examine the other knee.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported bilateral DLM prevalence of between 5 and 20 % in their respective populations [ 6 , 10 , 11 ]. Among studies conducted in East Asia, Kato et al used cadaveric knees to study the prevalence of lateral discoid menisci in the Japanese population [ 12 ]. They found that bilateral menisci were of homotype (the same shape) in knees of 253 of 279 (91 %) Japanese cadavers [ 12 ], and South Korean studies reported the prevalence of bilateral DLM to be between 79 % and 97 % for patients with unilateral symptomatic DLM [ 3 , 13 ].…”
Section: Introductionmentioning
confidence: 99%